The Association between Depression and Type 1 Diabetes Mellitus: Inflammatory Cytokines as Ferrymen in between? - Kexin Wang; Fangna Li; Yixin Cui; Chunhui Cui; Zhenzhen Cao; Kai Xu; Shuhong Han; Ping Zhu; Yu Sun (Hindawi Limited, 2019)
The depression incidence is much higher in patients with diabetes mellitus (DM), and the majority of these cases remain under-diagnosed. Type 1 diabetes mellitus (T1D) is now widely thought to be an organ-specific autoimmune disease. As a chronic autoimmune condition, T1D is characterized by T cell-mediated selective loss of insulin-producing β-cells. The age of onset of T1D is earlier than T2D, and T1D patients have an increased vulnerability to depression due to its diagnosis and treatment burden occurring in a period when the individuals are young. The literature has suggested that inflammatory cytokines play a wide role in both diseases. In this review, the mechanisms behind the initiation and propagation of the autoimmune response in T1D and depression are analyzed, and the contribution of cytokines to both conditions is discussed. This review outlines the immunological mechanism of T1D and depression, with a particular emphasis on the role of tumor necrosis factor-α (TNF-α), IL-1β, and interferon-γ (IFN-γ) cytokines and their signaling pathways. The purpose of this review is to highlight the possible pathways of the cytokines shared by these two diseases via deciphering their cytokine cascades. They may provide a basic groundwork for future study of the possible mechanism that links these two diseases and to develop new compounds that target the same pathway but can conquer two diseases.